A fluidez identitária em Memorial do Convento, de José Saramago - Cabral, Thaíla Moura (2018)
This research presents some impacts of the Post-modernity in the literary art, highlighting the identity fluidity of the main characters of the novel Memorial do convento (1982), namely: Bartolomeu Lourenço de Gusmão, Blimunda Sete-Luas e Baltasar Mateus Sete-Sóis. This study aims to understand the fragmentation of these main characters that go beyond their time. The first one, who is a priest and also a man of the science, lives the conflict between faith, dogma and reason; furthermore, he wants to be able to fly, in a time when mankind did not have the technology needed to navigate through the air. The second character is a woman, who was able to see beyond what physical vision could, conflicted between closing her eyes to the ignorance and experimenting the pain that knowledge and wisdom may cause. Baltasar, on the other hand, was a crippled former soldier who found in the construction of the time machine a blow of consciousness about his role in the universe. We aim to describe a smooth identity profile of these personalities and the manner in which their identities are shown throughout the narrative. For the realization of this study we chose the studies by theoreticians like: Jean-François Lyotard (1986), Zygmunt Bauman (2009, 2005, 2001, 1998) e Stuart Hall (2002, 2002, 1997), to talk about Post-Modernity, and consequently, about identity; and Jacques Le Goff (2013), Linda Hutcheon (2000, 1991) e Peter Burke (1992) to talk about the aspects of History and the Historiographic Metafiction. We also used the critical contributions of the following scholars: Ana Paula Arnaut (2008), Vera Bastazin (2006), Carlos Reis (2008, 2004) and João Marques Lopes (2010), who helped us comprehend in Saramago’s writing, which is singular and innovative, the legacy of his books for global literature.